Decreased diffusion capacity on lung function testing in asymptomatic patients with systemic lupus erythematosus does not predict future lung disease. (August 2015) - Elalouf, O; Fireman, E; Levartovsky, D; Kaufman, I; Rogovski, O; Elkayam, O; Caspi, D; Paran, D
Background: In a previous study performed 9 ± 3.6 years ago, 74 asymptomatic patients with systemic lupus erythematosus (SLE) and/or antiphospholipid syndrome (APS) underwent lung function testing. A significantly low diffusion capacity (DLCO) ranging from 45% to 70% was recorded in 28 of the 74 (37.8%) patients who were all free of respiratory symptoms. Aim: The aim of this report is to assess the clinical importance and the predictive value of a low DLCO in asymptomatic patients with SLE or APS. Methods: Asymptomatic patients with SLE and/or APS who were found to have a low DLCO in the previous study were contacted. Of the 28 patients, 15 were recruited and reevaluated in the current study (SLE with APS ( n  = 7), SLE without APS ( n  = 7); primary APS ( n  = 1)). A full history, physical examination, nail bed capillaroscopy, current laboratory tests and full lung function tests including DLCO were performed. Results: During a surveillance period of 9 ± 3.6 years, none of the patients developed lung disease. Diffusion capacity corrected for alveolar volume (DLCO/VA) improved in the study group during this period from 60.4% ± 7.0 to 76.1% ± 11.2 ( p  < 0.0001). Lung function tests including total lung capacity (TLC) and forced expiratory volume in one second (FEV1) remained within normal limits. Capillaroscopy studies did not reveal changes compatible with scleroderma in any of the patients. Conclusion: Low DLCO findings on lung function testing does not have a positive predictive value for the development of future lung disease in patients with SLE, with or without APS, who are free of respiratory symptoms. Our results suggest that a finding of low DLCO in asymptomatic patients with SLE, with or without APS, does not necessarily require further evaluation and imaging and may improve spontaneously over time. Further studies in a larger group of patients are needed to validate these findings.